Business resilience skills for SMEs - Panagiotis Kotsios (Journal of Innovation and Entrepreneurship, 2023)
The goal of this research was to investigate the skills and values that can be related to building resilient Small and Medium Enterprises. Primary data on the topic were collected through survey research in a sample of 266 Greek and Polish business owners and managers during the summer of 2020. According to the replies, the Personal characteristics and Values category had the highest importance levels, but their adequacy levels were high as well. Especially Reliability, Integrity and Work ethics have been pointed out as vital for the long-term viability of a business while facing crises situations. The largest mismatch between importance and adequacy, by order of importance, were Communication, Risk identification and assessment, Financial Management, Planning and organisation and Customer-orientation, and these may constitute priority areas for inclusion in business training programs.
Keywords: 650; Resilience; Survey; Greece; Poland; Skills